Pharmacological Inhibition of HMGB1 Prevents Muscle Wasting - Li, Lu; Liu, Huiquan; Tao, Weili; Wen, Su; Fu, Xiaofen; Yu, Shiying (Frontiers in Pharmacology, 2021)
Background: Cachexia is a multifactorial disorder characterized by weight loss and muscle wasting, making up for about 20% of cancer-related death. However, there are no effective drugs to combat cachexia at present. Methods: In this study, the effect of CT26 exosomes on C2C12 myotubes was observed. We compared serum HMGB1 level in cachexia and non-cachexia colon cancer patients. We further explored HMGB1 expression level in CT26 exosome. We added recombinant HMGB1 to C2C12 myotubes to observe the effects of HMGB1 on C2C12 myotubes and detected the expression level of the muscle atrophy-related proteins. Then, we used the HMGB1 inhibitor glycyrrhizin to reverse the effects of HMGB1 on C2C12 myotubes. Finally, HMGB1 inhibitor glycyrrhizin was utilized to relieve cachexia in CT26 cachexia mouse model. Results: Exosomes containing HMGB1 led to muscle atrophy with significantly decreased myotube diameter and increased expression of muscle atrophy-related proteins Atrogin1 and MuRF1. Further, we detected that HMGB1 induced the muscle atrophy mainly via TLR4/NF-κB pathway. Administration of the HMGB1 inhibitor glycyrrhizin could relieve muscle wasting in vitro and attenuate the progression of cachexia in vivo. Conclusion: These findings demonstrate the cachectic role of HMGB1, whether it is soluble form of HMGB1 or secreted from tumor cells as part of exosomes. HMGB1 inhibitor glycyrrhizin might be a promising drug in colon cancer cachexia.